Immersion of complete digraphs in Eulerian digraphs - Girao, Antonio; Letzter, Shoham (Arxiv, 2022)
A digraph G immerses a digraph H if there is an injection f : V (H) → V (G) and a collection of pairwise edge-disjoint directed paths Puv, for uv ∈ E(H), such that Puv starts at f (u) and ends at f (v). We prove that every Eulerian digraph with minimum out-degree t immerses a complete digraph on Ω(t) vertices, thus answering a question of DeVos, McDonald, Mohar, and Scheide.
Online veröffentlicht am 31. August 2021
Gesehen am 11.01.2024